An observed association between conjunctivitis and severity of COVID-19. Issue 3 (September 2021) - Loffredo, Lorenzo; Oliva, Alessandra; Paraninfi, Aurora; Ceccarelli, Giancarlo; Orlando, Federica; Ciacci, Paolo; Pacella, Fernanda; Pacella, Elena; Bari, Silvia Di; Filippi, Valeria; Cruciata, Alessia; Mastroianni, Claudio Maria; et al.
Highlights: Conjunctivitis could be a manifestation of systemic disease in COVID-19 patients. COVID-19 patients with conjunctivitis have increased mortality. COVID-19 patients with conjunctivitis have increased intensive care unit hospitalization. Graphical abstract: Image, graphical abstract